What causes Mars' annular polar vortices?. Issue 1 (10th January 2017) - Toigo, A. D.; Waugh, D. W.; Guzewich, S. D.
Abstract: A distinctive feature of the Martian atmosphere is that the winter polar vortices exhibit annuli of high potential vorticity (PV) with a local minimum near the pole. These annuli are seen in observations, reanalyses, and free‐running general circulation model simulations of Mars, but are not generally a feature of Earth's polar vortices, where there is a monotonic increase in magnitude of PV with latitude. The creation and maintenance of the annular polar vortices on Mars are not well understood. Here we use simulations with a Martian general circulation model to the show that annular vortices are related to another distinctive, and possibly unique in the solar system, feature of the Martian atmosphere: the condensation of the predominant atmospheric gas species (CO2 ) in polar winter regions. The latent heat associated with CO2 condensation leads to destruction of PV in the polar lower atmosphere, inducing the formation of an annular PV structure. Key Points: The winter polar vortices in the Martian atmosphere exhibit annuli of high potential vorticity with a local minimum near the pole Latent heating associated with CO2 condensation leads to the formation of an annular potential vorticity structure The existence of annular vortices on other planetary bodies may be related to condensation of atmospheric gas species in polar regions